Metafory pamięci (Instytut Badań Literackich Polskiej Akademii Nauk, 2024)
Pierre Nora, one of the prophets of the memory turn in culture, history and science, described our times as a 'time of memory'. Nearly 150 years ago, Julian Ursyn Niemcewicz wrote down an almost identical thought: ‘We live in the time of memoirs’. This volume attempts to recount the presence of memory issues in nineteenth-century consciousness. However, it deliberately – if not counting minor exceptions – forgoes those areas where these references are easiest to diagnose, i.e. in fiction and diarism. The 'metaphors' of the title, inspired by the work of the historian of psychology Douwe Draaisma, are peculiar glasses through which memory is viewed – a phenomenon so close to everyone and yet so obscure that it is usually necessary to use non-direct ways to better grasp it. Examples of such metaphors include a wax seal, a book, a garden, a calendar, a labyrinth, a coin or a medal, an exhibition of memorabilia, a grave, a prison, a journey, a daguerreotype; metaphors are present also in medical and neurological treatises. A particular way of conceptualising memory were the mnemonic theories developed at the time, to which a separate section is devoted. The book also contains translations of texts made by the author of the anthology (either as a whole or in fragments), which make it possible to present the issue of memory in a slightly broader context.